Computational Modelling of Sub-ordnance Velocity Impact of Conico-cylindrical Projectile with Semi-Infinite Target. (2017) - Trigunayak, Ankur; Dubey, Devendra K.; Chawla, Anoop
Abstract: This work demonstrates a methodology to analyze small time deformations in conico-cylindrical, multi-material projectile containing explosive material during sub-ordnance velocity impact with the semi-infinite target as hard soil. A 3-Dimensional computational model is developed and analysed using explicit analysis in ANSYS AUTODYN Hydrocode for the Lagrangian domain. The problem was studied for two extreme cases by varying the angle of impact between 0 0 -15 0 . Deformation and stress propagation patterns are studied in the projectile structure for impact with various targets like sand, concrete, and hard soil. To simulate this millisecond impact phenomenon, Mie-Gruneisen Shock-EOS was selected, strength model for the plastic deformation in ductile materials of the projectile was defined by Johnson –Cook Model and failure criteria defined for failure strain by J-C damage model. To define target as semi-infinite hard soil, compaction model was chosen. Pressure and energy variation with time at different points were observed and analysed for a critical condition for initiation of the explosion. This paper exhibits 3-D impact simulation methodology where deformation in projectile and target both considered for sub-ordnance velocity range impact.